Involvement of IL-13 and Tissue Transglutaminase in Liver Granuloma and Fibrosis after Schistosoma japonicum Infection. (3rd July 2014) - Tang, Juanjuan; Huang, Huayi; Ji, Xiaofang; Zhu, Xunmin; Li, Yinyan; She, Mingmin; Yan, Suikai; Fung, Mingchiu; Li, Zi
Abstract : Schistosomiasis, one of the most devastating parasitic diseases, is caused by Schistosoma japonicum ( Sj ) infection resulting in serious liver fibrosis. Interleukin- (IL-) 13, which is produced by T H 2   cells, is a critical profibrotic cytokine found in various organs, including the liver. Tissue transglutaminase (tTG), a group of multifunctional enzymes, serves a central function in the pathogenesis of chronic liver diseases. However, the relationship between IL-13, tTG, and liver fibrosis during Schistosoma infection has not been established. This study investigated the involvement of IL-13 and tTG in liver fibrogenesis during Sj infection in mice. Five weeks after Sj infection, granuloma and fibrosis development in the liver coincided with an increase in IL-13 and tTG in the liver and the upregulation of serum IL-13 in infected mice. Administration of cystamine, an inhibitor of tTG, abrogated the increase in both tTG and IL-13 in infected mice and ameliorated liver fibrogenesis and granuloma development. This result establishes a novel link among IL-13, tTG, and liver granuloma and fibrosis under Sj infection. Based on their important functions in liver fibrosis induced by Sj infection, IL-13 and tTG could be promising potential drug targets against schistosomiasis.